Magnetic Field Analysis around SUTT 150 Kv - Masita, Yulia; Solihah, Nadyatus; Zahra, Aldora Zori Aretha; Sudarti, Sudarti; Yushardi, Yushardi (Peneliti.net, 2026)
This article describes the results of a study on the measurement and analysis of magnetic fields in the area around a 150 kV High Voltage Overhead Line (SUTT). The main objective of this study is to assess the magnitude of the magnetic field generated by the SUTT and its potential impact on the environment. The approach used includes direct measurements using special equipment at a number of locations along the SUTT route. The results obtained show that the intensity of the magnetic field varies depending on the proximity of the measurement point to the SUTT, with the highest values ​​recorded at the closest location and decreasing significantly at further distances. The analyzed data show that the detected magnetic field is still within the acceptable threshold based on applicable standards. These findings provide an important picture of the impact of the presence of a 150 kV SUTT on the surrounding environment, and emphasize the importance of continuous monitoring to ensure that the magnetic field level remains safe. This study is expected to be a reference in the management and planning of electricity systems in the future.